Response of SOI microdosimeter in fast neutron beams: experiment and Monte Carlo simulations. (October 2021) - Vohradsky, James; Tran, Linh T.; Guatelli, Susanna; Chartier, Lachlan; Vandevoorde, Charlot; de Kock, Evan Alexander; Nieto-Camero, Jaime; Bolst, David; Peracchi, Stefania; Höglund, Carina; Rosenfeld, Anatoly B.
Highlights: Benchmark comparison of Geant4 and MCNP6 in characterisation of fast neutron beam. SOI Bridge microdosimeter measured experimentally and compared with the two codes. Neutron capture products from p+ B-implanted regions of the Bridge was investigated. Abstract: In this study, Monte Carlo codes, Geant4 and MCNP6, were used to characterize the fast neutron therapeutic beam produced at iThemba LABS in South Africa. Experimental and simulation results were compared using the latest generation of Silicon on Insulator (SOI) microdosimeters from the Centre for Medical Radiation Physics (CMRP). Geant4 and MCNP6 were able to successfully model the neutron gantry and simulate the expected neutron energy spectrum produced from the reaction by protons bombarding a 9 Be target. The neutron beam was simulated in a water phantom and its characteristics recorded by the silicon microdosimeters; bare and covered by a 10 B enriched boron carbide converter, at different positions. The microdosimetric quantities calculated using Geant4 and MCNP6 are in agreement with experimental measurements. The thermal neutron sensitivity and production of 10 B capture products in the p+ boron-implanted dopant regions of the Bridge microdosimeter is investigated. The obtained results are useful for the future development of dedicated SOI microdosimeters for Boron Neutron Capture Therapy (BNCT). This paper provides a benchmark comparison of Geant4 and MCNP6 capabilities in the context of further applications of these codes for neutron microdosimetry.